Kamus Bali-Indonesia Bidang Istilah Upakara Manusa Yadnya Di Kabupaten Badung - Krisna Aprianti, Putu; Sulibra, I Ketut Ngurah; Suryati, Ni Made (Humanis, 2016)
Research dictionary Balinese-Indonesia classified for terminology upakara manusa yadnya in Badung Regency, to have special purpose to know the shape and quantity of terminology in upakara manusa yadnya in Badung Regency. It is used linguistic structural theory by Ferdinand de Saussure, lexicology theory, and lexicograpy theory. In act of preparing data, it is used interview and see method, with tap technique. Followed record technique and note technique. In analysis data is used (1) translasional method followed by based technique classify determine element with intermediate technique, related equivalent technique make the same with related equivalent technique compare the main thing. (2) apportion method with based technique for element direct with intermediate technique are expansion technique and infix technique. Method that used in presentation analysis result is formal method and informal with inductive and deductive technique. The result of this research is terminolgy in form of based word consist of based word in one word, two word, three word, four word. From the based word can make new word. Affixs consist of : preffixs N-, {-paN}, {m?-}; suffixs {-an}; konffixs {pa-/-an}, and also combination affixs, the word that replay consist of : whole reduplication, whole reduplication + affixs, partial reduplication, partial reduplication + affixs, and word complex. Terminology in form of phrase is: endosentrik phrase just one main word consist of: nominal phrase, numeralia phrase, and verbal phrase. This research collect 402 terminology.